Comparison of CT-guided thoracic sympathetic nerve block and radiofrequency in the treatment of primary palmar hyperhidrosis - Zhang, Li; Xu, Shuang-shuang; Liu, Xiao-lan; Zhao, Wei; Ma, Ying; Huang, Bing (Frontiers in Surgery, 2023)
Background: Primary palmar hyperhidrosis (PPH) is a condition marked by an overactive secretion of the hand's exocrine glands and is frequently hereditary. The profuse sweating associated with this condition can significantly impair the patient's daily activities and quality of life. Objective: The objective of this study was to compared the benefits and drawbacks of thoracic sympathetic block and thoracic sympathetic radiofrequency in the treatment of PPH. Methods: A retrospective analysis was conducted on 69 patients. They were divided into groups A and B according to their treatment. Group A (34 cases) received CT-guided percutaneous thoracic sympathetic nerve chain anhydrous alcohol chemical damage block, and group B(35 cases)received CT-guided percutaneous thoracic sympathetic nerve chain radiofrequency thermocoagulation. Results: Palmar sweating disappeared immediately after the operation. The recurrence rates at 1, 3, 6, 12, 24, and 36 months were 5.88% vs 2.86%(P>0.05), 20.59% vs 5.71%(P>0.05), 32.35% vs 11.43%(P<0.05),32.35% vs 11.43%(P<0.05), 25% vs 14.71%(P<0.05), and 68.75% vs 20.59%(P<0.05), respectively. The incidence of intercostal neuralgia and compensatory hyperhidrosis was higher in group A compared with of group B(52.94% vs 22.86%, P<0.05; 55.88% vs 22.86%, P<0.05). Conclusion: Both methods were found to be effective in treating PPH, but thoracic sympathetic radiofrequency had a longer-term effect, a lower recurrence rate, and a lower incidence of intercostal neuralgia and compensatory hyperhidrosis than a thoracic sympathetic block.